2019
DOI: 10.1155/2019/6508261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training for Finger Perception on Functional Recovery of Hemiplegic Upper Limbs in Acute Stroke Patients

Abstract: Background Stroke causes severe disability, including motor and sensory impairments. We hypothesized that upper limb functional recovery after stroke may be augmented by combining treatments for motor and sensory functions. In order to examine this hypothesis, we conducted a controlled trial on rehabilitation for sensory function to the plegic hand. Methods The sensory training program consisted of several types of discrimination tasks performed under blind conditions. The sensory training program was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Findings particularly suggest the importance of somatosensory function after stroke for recovery of precision grip force control [12], safety and dexterity in the paretic hand [13] and functional independence in activities of daily living (ADL) [14,15]. Current findings showed that active and passive sensory retraining may be an effective intervention for improving the light touch threshold of the hand, dexterity, upper extremity (UE) motor function [10,16] to improve the activity of daily living in stroke patients with impaired sensory motor abilities [17]. The quality of evidence is low to moderate [18,19] so further research is required to determine the effectiveness of sensory training in stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Findings particularly suggest the importance of somatosensory function after stroke for recovery of precision grip force control [12], safety and dexterity in the paretic hand [13] and functional independence in activities of daily living (ADL) [14,15]. Current findings showed that active and passive sensory retraining may be an effective intervention for improving the light touch threshold of the hand, dexterity, upper extremity (UE) motor function [10,16] to improve the activity of daily living in stroke patients with impaired sensory motor abilities [17]. The quality of evidence is low to moderate [18,19] so further research is required to determine the effectiveness of sensory training in stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 85%
“…Deficits in somatic sensations (body senses such as touch, temperature, pain, and proprioception) after stroke are common with prevalence rates variously reported to be 11-85% [8]. Approximately 50% of stroke patients have hand sensory impairments, especially in tactile and proprioceptive discrimination [9,10]. Sensation is essential for safety even if there is adequate motor recovery [11].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 38 included studies, 24 were longitudinal cohort studies in which muscle characteristics were measured at least twice within 3 months post-stroke (31, 33-36, 39, 41, 42, 44, 46, 48, 50, 52-55, 57, 58, 60-62, 64, 65, 67). The remaining eligible studies represent 13 randomized controlled trials (RCTs) (32,37,38,40,43,45,47,49,51,59,63,66,68) and 1 clinical controlled trial (CCT) (56). Participants in the control groups of these interventional trials were considered as longitudinal data as they received conventional physiotherapy…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal muscle changes in the first 3 months of stroke recovery p. 7 of 19 Statistically significant Studies reporting differences between the paretic and non-paretic side are marked with † (no difference between both sides (p≥0.05)) or ‡ (significant difference between both sides (p < 0.05)). (32,37,38,40,47,49,56,59,63,66,68) or a placebo intervention combined with usual care (32,43,45,51).…”
Section: Journal Of Rehabilitation Medicinementioning
confidence: 99%
“…Sensory de cits may also lead to reduced nger control. Umeki et al [28] conducted sensory training to enhance nger discrimination in patients and found that the mean change in tactile pressure threshold was signi cantly greater in the experimental group than in the control group. The reduction in manipulation time required for handling small balls and small metal discs that was observed in the experimental group was signi cantly greater than that observed in the control group.…”
Section: Underlying Neurophysiological Mechanisms Of Performance De Citsmentioning
confidence: 99%